Pathistological investigation of the influence of the adrenoblocator complex on regeneration of the mandible bone - Kononova, O. (Actual Dentistry, 2018)
Abstract. In the development of periodontal diseases, the presence of psychological stress in patients is important. This should be taken into account in the complex treatment of patients with periodontal disease. For the effective treatment of periodontal diseases in these patients, it is necessary to experimentally validate the effectiveness of the proposed complex of adrenoblockers. Objective: experimentally substantiate the effect of the proposed drug composition on the regeneration of the artificially created defect of the mandible bone in rats when they model adrenalin stress. Methods. To substantiate the effectiveness of the proposed complex of adrenoblockers for the treatment of periodontal diseases, an experimental animal study was conducted. Adrenalin stress was modeled in rats by oral administration of gel with adrenaline at a dose of 0.36 mg/kg for 10 days. Lincomycin was taken with drinking water at a dose of 60 mg/kg. The animals formed a defect in the mandible bone, which was filled with the drug Bio-Oss. The gel of adrenoblockers (zoxon + nicergolin and sibazon) was administered by application at a dose of 0.6 mg / kg. Histological bone studies were performed in 10 and 30 days using hematoxylin and eosin. Results. The conducted experimental studies have shown that the development of adrenaline stress inhibits regeneration of the mandible bone. The applications of adrenoblockers stimulate the regeneration of the experimental defect of the mandible bone. Conclusions. Oral administration of gel with adrenoblockers stimulates bone regeneration in the area of an experimental defect of the mandible. Key words: generalized periodontitis, adrenalin stress, adrenoblockers.